ChemInform Abstract: Synthesis of Pyrazolo[1, 2‐a]cinnolines via a Rhodium‐Catalyzed Oxidative Coupling Approach. Issue 35 (2nd September 2014) - Xing, Li; Fan, Zhoulong; Hou, Chengyu; Yong, Guoping; Zhang, Ao
Abstract The oxidative coupling of N‐arylpyrazolones with terminal alkynes tolerates various substituents in both partners and provides a broad range of pyrazolocinnoline derivatives.